Expected Limits on the Potential for Carbon Dioxide Removal From Artificial Upwelling - Koweek, David A. (Frontiers in Marine Science, 2022)
Artificial upwelling, the engineered upward pumping of deep ocean water, has long been proposed as a technique to fertilize the ocean and, more recently, remove atmospheric carbon dioxide. This study investigated the potential of artificial upwelling to contribute to carbon dioxide removal using a simple model with high-resolution (1° × 1°) gridded monthly climatologies of upper ocean and deep ocean physical and chemical properties. The potential for carbon dioxide removal was explored across a range of observationally-informed carbon-to-nitrogen-to-phosphorus ratios for microalgae and macroalgae communities, providing information on the sensitivity of the estimates to any assumed carbon-to-nutrient ratios. Simulated carbon dioxide removal across the tropical-to-subpolar ocean did not exceed 0.66 tons per square kilometer per year for microalgae, and did not exceed 0.85 tons per square kilometer per year for macroalgae. Using current technology, the estimated global aggregate potential for carbon dioxide removal using microalgae was less than 50 megatons (0.05 gigatons) of carbon dioxide annually and the estimated global aggregate potential for carbon dioxide removal using macroalgae was approximately 100 megatons (0.1 gigatons) of carbon dioxide annually. While controlled field trials are needed to validate or invalidate the findings of this study, this study suggests that artificial upwelling is unlikely to support annual carbon dioxide removal at, or close to, the rate of one gigaton of carbon dioxide annually.